Renewable microgrid operational results and economic evaluation using RETScreenTM - Edison Banguero; Hector David Agudelo Arias; Andres Julian Aristizabal; Daniel Hernán Ospina Baragán (Institute of Advanced Engineering and Science, 2019)
This article describes the performance results of the first renewable microgrid of Chocó, Colombia, monitored over two years (2016-2017) adding an economic approach. A virtual platform is used to analyze, in real time, the microgrid power production, while a meteorological station measures the solar irradiance and the ambient temperature. The results indicated that the generation of AC PV energy was 21,817 kWh/year on 2016 and 23,301 kWh/year on 2017. The photovoltaic system’s average efficiency was 10.3 % on 2016 and 11.09 % on 2017. An economical analysis of the renewable microgrid is also presented using RETScreenTM software. The results show a net present value of 237,028 USD for an evaluation period of 25 years with annual energy savings of 4,622 USD. A calculation on greenhouse gas emissions show that 22.9 tCO2 per year are avoided when using the solar energy tech.